Demystifying Leadership in Iceland An Inquiry into Cultural, Societal, and Entrepreneurial Uniqueness - Minelgaite, Inga (Contributions to Management Science,, 2018)
This book explores the nature and uniqueness of leadership in Iceland within a business and economic context. Starting with an analysis of Iceland's geographical location, historical development and societal culture, the authors critically examine the major elements of the Icelandic business environment from an individual to a global level, and from economic prosperity to financial collapse. They particularly focus on leadership and human resource management within this unique societal culture and discuss the specific issues that are unique to Iceland, i.e. entrepreneurship, gender egalitarianism, equality, low power-distance, reflecting on, and orienting within contemporary leadership theories. The book covers a variety of analytical methods and cases, providing a unique introduction to leadership in Iceland, and opening avenues for further research into this relatively new phenomenon.